Randomized clinical trial of comprehensive geriatric assessment and optimization in vascular surgery. Issue 6 (15th February 2017) - Partridge, J. S. L.; Harari, D.; Martin, F. C.; Peacock, J. L.; Bell, R.; Mohammed, A.; Dhesi, J. K.
Abstract: Background: Increasing numbers of older patients are undergoing vascular surgery. Inadequate preoperative assessment and optimization may contribute to increased postoperative morbidity and mortality. Methods: Patients aged at least 65 years scheduled for elective aortic aneurysm repair or lower‐limb arterial surgery were enrolled in an RCT of standard preoperative assessment or preoperative comprehensive geriatric assessment and optimization. Randomization was stratified by sex and surgical site (aorta/lower limb). Primary outcome was length of hospital stay. Secondary outcome measures included new medical co‐morbidities, postoperative medical or surgical complications, discharge to a higher level of dependency and 30‐day readmission rate. Results: A total of 176 patients were included in the final analysis (control 91, intervention 85). Geometric mean length of stay was 5·53 days in the control group and 3·32 days in the intervention group (ratio of geometric means 0·60, 95 per cent c.i. 0·46 to 0·79; P < 0·001). There was a lower incidence of delirium (11 versus 24 per cent; P = 0·018), cardiac complications (8 versus 27 per cent; P = 0·001) and bladder/bowel complications (33 versus 55 per cent; P = 0·003) in the intervention group compared with the control group. Patients in the intervention group were less likely to require discharge to a higher level of dependency (4 of 85 versus 12 of 91; P = 0·051). Conclusion: In this study of patients aged 65 years or older undergoing vascular surgery, preoperative comprehensive geriatric assessment was associated with a shorter length of hospital stay. Patients undergoing assessment and optimization had a lower incidence of complications and were less likely to be discharged to a higher level of dependency. Registration number: ISRCTN23142588 (http://www.controlled-trials.com ). Abstract : Better outcomes